Experimental Study of Energy Dissipation at Baffled Chute Spillway - Nugroho, Joko (Institut Teknologi Bandung, 2019)
Experimental observation on a model of free over flow spillway is used in this study. Three configurations of baffle placement are used in the experiment. The energy along the flow over the spillway were calculated based on measured flow depth and discharge during the experiment. Variations of flow depth and discharge were determined based on baffle height as a reference. The experiments were done in a 7 meters long flume of 0.078 m wide. The spillway model has a dimension of 17.2 cm high, with rounded crest and 1:1 downstream slope. There is no structures placed at the downstream of spillway. The discharge applied to the spillway model is in the range of 0.6 to 1.8 l/s. The experimental results shows that optimum results of energy dissipation were obtained when the flow depth is equal to the height of the baffle. Observed energy dissipations in this is in the range of 30% to 50% upon the incoming energy of the spilled flow. It was also observed that the length of the hydraulic jumped is reduced due to the application of baffled chute.